2005
DOI: 10.2320/matertrans.46.909
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rhenium and Cooling Rate on the Solidification of Ni Base Superalloys, Inconel 718

Abstract: Influence of 2-6% Re additions has been investigated on the solidification phenomenon of a Ni base superalloy, In718. The solidification of each alloy proceeds in the order of primary , eutectic (+NbC) and eutectic (+Ni 2 Nb). Higher additions of Re increase the volume fraction of primary and enlarge the secondary dendrite arm spacing. The influence of cooling rates at 1, 10 and 100 K/min has also been studied on the solidification process of the alloy containing 3.5% Re. With increasing cooling rate, the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The width of columnar/cellular structures increases with increasing Re content ( Figure 5) from 893 ± 223 to 1936 ± 515 nm observed for IN718 and IN718-6Re, respectively. A similar effect of Re addition was observed by El-Bagoury et al [40] for cast IN718 alloy. Higher Re content resulted in the increased volume fraction of c phase and enlarged dendrite arm spacing.…”
Section: B Microstructure Of In718-re Alloyssupporting
confidence: 86%
“…The width of columnar/cellular structures increases with increasing Re content ( Figure 5) from 893 ± 223 to 1936 ± 515 nm observed for IN718 and IN718-6Re, respectively. A similar effect of Re addition was observed by El-Bagoury et al [40] for cast IN718 alloy. Higher Re content resulted in the increased volume fraction of c phase and enlarged dendrite arm spacing.…”
Section: B Microstructure Of In718-re Alloyssupporting
confidence: 86%
“…the microsegregation would be negligible depending on the diffusivity of each solute element when the cooling rate is increased up to a certain limit. [16,30,33,34] The back-diffusion effect with respect to the cooling rate in CMSX-10 and CMSX-4 can be qualitatively evaluated on the basis of c/c¢ eutectic volume fraction, because all the c¢ forming elements in both alloys were found to be segregated to liquid during the solidification of primary c (Table II). Figure 10 shows a schematic illustration of the back-diffusion effect on the formation of c/c¢ eutectic, which is based on the quasi-binary Scheil model.…”
Section: Effect Of Back-diffusion and Dendrite Arm Coarseningmentioning
confidence: 99%
“…It has been known that the extent of back-diffusion in solid during solidification is proportional to the local solidification times and the diffusivity of solute element in solid ( s ), while it is inversely proportional to the square of the diffusion distance and the cooling rate ( [26]. Regarding the influence of the cooling rate on the extent of back-diffusion, El-Bagoury et al [27] have recently shown that the microsegregation of Nb between the dendrite core and interdendritic region decreases at lower cooling rate of about 1.0 K/min by back-diffusion in alloy IN718. However, they have Table III.…”
Section: Effect Of Back-diffusion During Dendritic Solidificationmentioning
confidence: 99%